Unravelling turbot (Scophthalmus maximus) resistance to Aeromonas salmonicida: transcriptomic insights from two full-sibling families with divergent susceptibility - Pereiro, Patricia; Tur, Ricardo; García, Miguel; Figueras, Antonio; Novoa, Beatriz (Frontiers in Immunology, 2024)
IntroductionFurunculosis, caused by the gram-negative bacterium Aeromonas salmonicida subsp. salmonicida, remains a significant threat to turbot (Scophthalmus maximus) aquaculture. Identifying genetic backgrounds with enhanced disease resistance is critical for improving aquaculture health management, reducing antibiotic dependency, and mitigating economic losses. MethodsIn this study, five full-sibling turbot families were challenged with A. salmonicida, which revealed one family with significantly greater resistance. Transcriptomic analyses (RNA-Seq) were performed on resistant and susceptible families, examining both naïve and 24-h postinfection (hpi) samples from head kidney and liver tissues. ResultsIn the absence of infection, differentially expressed genes (DEGs) were identified predominantly in the liver. Following infection, a marked increase in DEGs was observed in the head kidney, with many genes linked to immune functions. Interestingly, the resistant family displayed a more controlled inflammatory response and upregulation of genes related to antigen presentation and T-cell activity in the head kidney at early infection stages, which may have contributed to its increased survival rate. In the liver, transcriptomic differences between the families were associated mainly with cytoskeletal organization, cell cycle regulation, and metabolic processes, including insulin signalling and lipid metabolism, regardless of infection status. Additionally, many DEGs overlapped with previously identified quantitative trait loci (QTLs) associated with resistance to A. salmonicida, providing further insights into the genetic basis of disease resistance. DiscussionThis study represents the first RNA-Seq analysis comparing resistant and susceptible turbot families and contributes valuable knowledge for the development of selective breeding programs targeting disease resistance in turbot and other aquaculture species susceptible to A. salmonicida.